2022
DOI: 10.1002/mde.3703
|View full text |Cite
|
Sign up to set email alerts
|

Who is more aggressive under vertical product differentiation?

Abstract: In this paper, we introduce quality differences in vertical market and compare the managerial delegation contracts of downstream firms. We find that the owner of a downstream firm that produces low‐quality products induces the manager to behave more aggressively when the marginal cost coefficient is low. While when marginal cost coefficient is high, the owner of a downstream firm that produces high‐quality products induces the manager to behave more aggressively. It is further found that managerial delegation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Without loss of generality, it is assumed that the quality of product produced by firm 1is lower than firm 2, that is, θ2θ1=δ, where δ denotes the difference in product quality. Similar to Wang (2023a), we assume that consumers are uniformly distributed on the line l[]0,1, and consumers have different preferences for product quality depending on their location. When a consumer at xl purchases product produced by firm i()i=1,2, the consumer's utility function is u=θixpi()i=1,2, where pi represents the product price.…”
Section: Basic Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Without loss of generality, it is assumed that the quality of product produced by firm 1is lower than firm 2, that is, θ2θ1=δ, where δ denotes the difference in product quality. Similar to Wang (2023a), we assume that consumers are uniformly distributed on the line l[]0,1, and consumers have different preferences for product quality depending on their location. When a consumer at xl purchases product produced by firm i()i=1,2, the consumer's utility function is u=θixpi()i=1,2, where pi represents the product price.…”
Section: Basic Modelmentioning
confidence: 99%
“…In general, managerial delegation contracts will reduce firm profits, thus making firms fall into a prisoner's dilemma (Colombo, 2022; Fershtman & Judd, 1987). Under the vertical market structure, Wang (2023a) found that managerial delegation can increase downstream firm profits. Existing literatures have analyzed the effect of production costs (Fanti & Meccheri, 2017; Hamamura & Ramani, 2023), horizontal shareholding (Nakamura, 2011), overinvestment (Pal, 2010), R&D spillover (Kräkel, 2004), corporate social responsibility (Fanti & Buccella, 2019), product quality (Wang & Wang, 2021), and market competition (Nakamura, 2017) on managerial delegation contracts.…”
Section: Introductionmentioning
confidence: 99%